A square-wave voltammetric method for analysing the colour marker quinizarine in petrol and diesel fuels - Trindade, Magno Aparecido Goncalves; Ferreira, Valdir Souza; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V., 2007)
This work presents an electroanalytical method based on square-wave voltammetry (SWV) for the determination of quinizarine (QNZ) in a mixture of Britton-Robinson buffer 0.08 mol L-1 with 30% of acetonitrile. The QNZ was oxidized at glassy carbon electrode in and the well-defined peak at +0.45 V vs. Ag/AgCl can be used for its determination as colour marker in fuel samples. All parameters were optimized and analytical curves can be constructed for QNZ concentrations ranging from 2.0 x 10(-6) mol L-1 to 1.4 x 10(-5) mol L-1, using f = 60 Hz and E-sw = 25 mV. The method offers a limit detection of 4.12 x 10(-7) mol L-1 and a standard deviation of 4.5% when six measurements of 1.25 x 10(-5) mol L-1 are compared. The method was successfully applied for determining QNZ in gasoline and diesel oil and the obtained results showed good agreement with those reported previously. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: quinizarine; marker; fuels; electroanalytical method